2010
DOI: 10.4314/eamj.v86i9.54165
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy rates among female participants in phase 1 and phase 2A AIDS vaccine clinical trials in Kenya

Abstract: Background: Female participants in AIDS candidate vaccine clinical trials must agree to use effective contraception to be enrolled into the studies, and for a specified period after vaccination, since the candidate vaccines' effects on the embryo or foetus are unknown. Objectives: To review data on female participants' pregnancy rates from phase I and IIA AIDS vaccine clinical trials conducted at the Kenya AIDS Vaccine Initiative (KAVI) and to discuss the challenges of contraception among female participants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Furthermore, frequently vaccination with recombinant MVA vaccines generally leads to a progressive reduced ability of such Immunogenics, probably because of the vector- related humoral responses [77,78]. Unsuccessful outcomes of clinical trial I of a MVA-based HIV vaccine [79,80] have suggested that scientists need more researches to better understanding about the key mechanisms of antigen presentation [81,82], immune system [83], and vector-specific antibody responses [84], so that it can be possible to increase the immunogenicity of presently accessible MVA vaccines [75,85].…”
Section: Modified Vaccinia Virus Ankara Vaccinementioning
confidence: 99%
“…Furthermore, frequently vaccination with recombinant MVA vaccines generally leads to a progressive reduced ability of such Immunogenics, probably because of the vector- related humoral responses [77,78]. Unsuccessful outcomes of clinical trial I of a MVA-based HIV vaccine [79,80] have suggested that scientists need more researches to better understanding about the key mechanisms of antigen presentation [81,82], immune system [83], and vector-specific antibody responses [84], so that it can be possible to increase the immunogenicity of presently accessible MVA vaccines [75,85].…”
Section: Modified Vaccinia Virus Ankara Vaccinementioning
confidence: 99%